FARMERS’ TRAIT PREFERENCES OF ORANGE-FLESHED SWEET POTATO IN ONDO STATE, NIGERIA - Obisesan, A.; Omosehin, O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analyzed trait preferences of Orange-Fleshed Sweet Potato (OFSP) among farmers in Ondo State, Nigeria. Data were collected through multistage sampling procedure using structured questionnaire. Descriptive statistics, factor analysis, and probit regression model were employed in the data analyses. The mean age of the farmers was 52 years. Most (90%) of the farmers were males with an average household size of 6 persons. The farmers were smallholders with average farm size of 0.62 hectares. The result revealed that majority (76%) of the farmers were aware of the OFSP variety, but only 58% of the respondents were adopters. The result of the probit regression model showed that sex (P< 0.1), membership of farmers’ association (P< 0.01) and credit access (P< 0.05) significantly increased adoption while age (P< 0.05) had negative influence on adoption of OFSP variety. Early maturity, yield, taste, ability to stay longer in the soil and drought tolerance were the traits considered by the farmers. From the factor analysis, ability to stay longer in the soil had the highest relevance, followed by drought tolerance while early maturity had the least relevance in the model. This revealed that OFSP farmers preferred a variety that has good in-soil storage traits to productivity traits. Therefore, the study recommends the prioritization of the preferred traits in the breeding of improved varieties in order to ensure demand-driven agricultural research and development.